Fees for uninsured services: a cross-sectional survey of Ontario family physicians - Daw, Jamie R. (CMAJ Open, 2020)
BACKGROUND: In Canada, family physicians are permitted to charge patient fees for administrative services that are not covered by the public health insurance program, such as prescription renewals outside of an office visit, and completion of forms and sick notes. The objective of this study was to estimate the proportion of Ontario family physicians who offer various fee structures (i.e., à la carte, annual block fees for all uninsured services rendered or no charge) for uninsured administrative services. METHODS: This was a cross-sectional telephone survey conducted from April to July 2019 of a random sample of family physicians licensed to practise in Ontario. We excluded physicians with missing contact information or additional specialties, or whose primary practice was outside of Ontario, with a walk-in clinic, with an emergency department, or with an organization that cared for a specific population (e.g., nursing home) or did not provide care (e.g., insurance company). We categorized the geographic location of practices as large urban centre (population > 100 000), small to medium centre (population 1000–99 999) or rural area. We calculated survey weights to account for nonresponse and to ensure representativeness of the sample by geographic area and payment model. RESULTS: Among the 221 physicians who met the inclusion criteria, the telephone was not answered at 42 practices, and the contact information was incorrect for 13, resulting in a sample of 166 physicians (response rate 75.1%). The majority of practices reported that they charged fees for uninsured services: 97 (58.3%, 95% confidence interval [CI] 50.6–65.8) charged à la carte, and 33 (20.3%, 95% CI 14.8–27.3) offered patients the option to pay an annual block fee; 19 (11.4%, 95% CI 7.4–17.3) charged no fees. Fee structures varied by geographic area but not physician payment model. INTERPRETATION: The use of à la carte and annual block fees for uninsured administrative services was commonly reported by a sample of Ontario family physicians. Further research is needed to examine the prevalence of patient payment of fees for uninsured services, patient and physician perceptions of fees, and concordance with regulatory guidance.